CALLY index predicts survival and surgical outcomes in colorectal cancer - Zong, Yunmeng; Wang, Yulong; Chen, Ying; Feng, Xiao; Jiang, Bin; Li, Yun (Frontiers in Nutrition, 2025)
BackgroundThe prognostic evaluation of colorectal cancer (CRC) traditionally relies on TNM staging, which fails to incorporate host-related factors such as systemic inflammation, nutrition, and immunity. The C-reactive protein–albumin–lymphocyte (CALLY) index has recently been proposed as a novel biomarker integrating these domains.MethodsWe retrospectively analyzed 957 patients with CRC undergoing curative resection (2010–2020). The CALLY index was calculated from preoperative laboratory data. Patients were stratified into high- and low-CALLY groups using ROC-derived cutoffs. Associations with postoperative complications, overall survival (OS), and disease-free survival (DFS) were assessed and compared with other indices (mGPS, PNI, NLR, PLR, SII, CAR).ResultsLow CALLY was significantly associated with higher complication rates (23.0% vs. 14.9%, p = 0.002), inferior OS and DFS (both log-rank p < 0.001), and remained an independent predictor in multivariable Cox and logistic models. Compared with other indices, CALLY demonstrated stronger discriminatory ability, achieving the highest AUC for 5-year OS, and its C-index value also outperformed other indices, further confirming the predictive efficacy of CALLY.ConclusionThe preoperative CALLY index is a simple, cost-effective, and reliable prognostic biomarker for CRC, predicting both surgical outcomes and long-term survival. Incorporation of CALLY into risk stratification may complement TNM staging, optimize perioperative management, and inform individualized treatment strategies. Further validation in multicenter, prospective cohorts is required to confirm the generalizability of these findings.